Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1073/pnas.211399398
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human heme oxygenase in endothelial cells by using sense and antisense retroviral constructs

Abstract: C ellular levels of heme are regulated by the rates of its synthesis and degradation. Heme catabolism occurs by oxidative cleavage of the ␣-methene bridge of the tetrapyrrole, eventually leading to the formation of equimolar amounts of biliverdin and CO and the release of the contained iron atom (1, 2). Biliverdin is then rapidly reduced to form bilirubin (3, 4). The heme oxygenase (HO) system controls the rate-limiting step in heme catabolism (5). To date, three HO isoforms (HO-1, HO-2, and HO-3) have been id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 34 publications
(31 reference statements)
4
51
0
Order By: Relevance
“…We also analyzed the 6-OHDA-induced HE incorporation in The antisense retroviral expression vector for HO-1 under the control of its own promoter (LSN-HOP-HHO-1-AS) has been described previously (27). In agreement with previous reports (36), cells transfected with this antisense constructs grew more slowly (data not shown), suggesting abnormalities in cell cycle progression.…”
Section: Induction Of Ho-1 Expression and Exogenous Addition Of Bilirsupporting
confidence: 86%
See 2 more Smart Citations
“…We also analyzed the 6-OHDA-induced HE incorporation in The antisense retroviral expression vector for HO-1 under the control of its own promoter (LSN-HOP-HHO-1-AS) has been described previously (27). In agreement with previous reports (36), cells transfected with this antisense constructs grew more slowly (data not shown), suggesting abnormalities in cell cycle progression.…”
Section: Induction Of Ho-1 Expression and Exogenous Addition Of Bilirsupporting
confidence: 86%
“…PC12 cells were infected with the retroviral expression vector LSN-HHO-1, which has been described previously (27). We could not find cell clones with levels of HO-1 overexpression higher than 2-3-fold, suggesting that higher constitutive levels of HO activity may be deleterious (see "Discussion"), probably as a result of the depletion of intracellular heme reservoirs.…”
Section: Induction Of Ho-1 Expression and Exogenous Addition Of Bilirmentioning
confidence: 76%
See 1 more Smart Citation
“…20,24 In contrast, endothelial cells infected with LSN-HO-1-AS demonstrated decreased HO-1 protein expression associated with a decrease in HO activity and an increase in heme content. [23][24][25][26] We also showed that the human HO-1 gene can be expressed in adult SHR by injecting the retroviral vector LSN-HHO-1 into newborns, 19 a method used by others, for example, to overexpress or suppress angiotensin receptors. 27 In a previous study, long-term expression of human HO-1 resulted in attenuation of hypertension in SHR.…”
Section: Discussionmentioning
confidence: 93%
“…6 According to a recent study, prostaglandin synthesis in rabbit coronary and human endothelial cells decreases in response to interventions that upregulate the expression of heme oxygenase (HO)-1. 7,8 HO isoforms -1 and -2 catalyze the metabolisms of heme to biliverdin and carbon monoxide (CO), respectively, an antioxidant and a vasoactive mediator. 9,10 HO isoforms, particularly HO-1, play a critical role in the regulation of cellular heme levels, 11 which in turn may impact on the expression of catalytically active COX isoforms.…”
mentioning
confidence: 99%